The Babylonian Dodecatemoria and Calendar Texts: Inverse Schemes for Determining Position and Times for the Schematic Sun and Moon - Brack-Bernsen, Lis (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2021)
The Dodecatemoria may be understood as a very simple reproduction of the Moon’s movement: for each day in the schematic year, the Dodecatemoria-scheme gives the position of the schematic Moon in the zodiacal circle. The Moon’s angular velocity was calculated as 13°/day and the Sun’s, as 1°/day. The scheme of the Calendar Texts may also be interpreted astronomically: for each position in the zodiacal circle, it gives the date at which the schematic Moon was in that position. We know that the schemes are inverse. A closer analysis of the texts accompanying the Calendar Text (LBAT 1586+1587) shows that the Babylonians also knew and utilized that fact as well.